About one boundary problem with overdeterminate conditions - Kvedaras, B. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Кведарас, Об одной краевой переопределенными условиями B. Kvedaras, Apie vieną kraštinį uždavinį su perapibrėžtomis sąlygomis